Emerging multinationals from China and Latin America: a comparative analysis. Issue 4 (2nd October 2018) - Casanova, Lourdes; Chen, Taotao; Chen, Chen; Xu, Run
Abstract: Latin American countries were pioneers in developing economies' outward foreign direct investment (OFDI) activities. Since late 1960s and early 1970s, Latin American countries led the first wave of OFDI from developing economies, steered mainly by Argentina and Brazil. Though they lost ground during debt crisis in 1980s, Latin American countries were catching up in OFDI since late 1990s. In contrast, China's participation in OFDI started much later, mainly after the year 2000 but hast accelerated very fast since 2008. Even though China and Latin American countries are the main investors from emerging markets, they have many differences in their outward foreign direct investment characteristics, capabilities and development paths. This paper analyses and compares the outward investment data of China and Latin American countries distinguishing the different internationalisation phases of both regions. It also looks at industrial and firm level characteristics analysing the Chinese Minmetals and the Brazilian Vale.